2005
DOI: 10.1007/s00026-005-0261-7
|View full text |Cite
|
Sign up to set email alerts
|

On the Number of Latin Squares

Abstract: We (1) determine the number of Latin rectangles with 11 columns and each possible number of rows, including the Latin squares of order 11, (2) answer some questions of Alter by showing that the number of reduced Latin squares of order n is divisible by f ! where f is a particular integer close to 1 2 n, (3) provide a formula for the number of Latin squares in terms of permanents of (+1, −1)-matrices, (4) find the extremal values for the number of 1-factorisations of k-regular bipartite graphs on 2n vertices wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
123
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 17 publications
(29 reference statements)
1
123
0
Order By: Relevance
“…However, latin squares, considered in their most general sense, arguably behave combinatorially rather than algebraically. For example, the number of latin squares of order n grows superexponentially in n, and most latin squares have a trivial autotopism group ( [55]). The focus of this survey is combinatorial.…”
Section: What Is a Partial Latin Square?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, latin squares, considered in their most general sense, arguably behave combinatorially rather than algebraically. For example, the number of latin squares of order n grows superexponentially in n, and most latin squares have a trivial autotopism group ( [55]). The focus of this survey is combinatorial.…”
Section: What Is a Partial Latin Square?mentioning
confidence: 99%
“…For example, there are exactly twelve latin squares of order 3: So to generate a random latin square of order 3, it suffices to index the above set of squares in a list of size 12, then select, at random, an integer from 1 to 12. However, M c K a y and W a n l e s s [55] recently showed that the number of latin squares of order 11 is: 776966836171770144107444346734230682311065600000.…”
Section: Generating Random Latin Squares Efficientlymentioning
confidence: 99%
“…[15]). In terms of running time, the entire computation (including the correctness checks described in what follows) took about 13 days on a Linux PC with a 3.66-GHz Intel Xeon CPU and 32 GB of main memory.…”
Section: Implementation Detailsmentioning
confidence: 99%
“…We call a Latin rectangle normalized if values 1, ..., n occur in the first row in natural order. Counting Latin rectangles is a topic broadly studied in combinatorics; some examples listed in chronological order are [16], [4], [7], [13] and [18]. Definition 1 Two m-row Latin rectangles of order n, with m < n, form an orthogonal pair (OLR) if and only if when superimposed each of the n 2 ordered pairs of values (1, 1), (1,2), ..., (n, n) appears at most once.…”
Section: Introductionmentioning
confidence: 99%